MODEL BRANDING SMART-Q SEBAGAI PENGUATAN SDM MADRASAH BERKARAKTER QUR’ANI - Rochmatul Muna; Mohamad Joko Susilo (STKIP Pesisir Selatan, 2026)
Madrasahs are expected to provide high-quality education while instilling Qur’anic values; however, in practice, there remains a gap between the ideal role of madrasahs and the actual conditions encountered in the field. MI Ma’arif Pijenan reflects this gap through limited facilities, declining student enrollment, and suboptimal quality of human resources, which have resulted in decreased public trust. To date, studies on madrasah quality improvement have generally positioned branding merely as an institutional promotional strategy, rather than as an integrated quality management system linked to human resource development and Qur’anic values. This study examines the implementation of SMART-Q branding (Spiritual, Moral, Academic, Relational, and Tahfidz Quality) as an effort to bridge this gap. The research employs a qualitative descriptive method with a case study approach. Data were collected through observation, interviews, documentation, and literature review, and analyzed using the Miles and Huberman model. The findings indicate that SMART-Q branding is able to strengthen madrasah quality holistically through the enhancement of spirituality, moral development, academic improvement, social relations, and the tahfidz program as a Qur’anic identity. The novelty of this study lies in conceptualizing branding as an integrated quality management system based on Qur’anic values, rather than merely as a promotional strategy